The Importance of Vertical and Horizontal Greening in The Republic of Uzbekistan Znachenie Vertikalnogo I Horizontalnogo Ozeleneniya V Republic of Uzbekistan the Significance of Vertical and Horizontal Greening in The Republic of Uzbekistan - Khamidov Famous Zarifovich; Kodirov Ahmadjon Abduraufovich; Shaymanov Sherzod Kamol o'g'li (Scientific Trends, 2022)
This in the article A wide variety of local and tropical plants are used for landscaping around the world about many data cause passed . According to the UN Convention on Biological Diversity, 34,000 species of plants are under threat of extinction in recent years. The emergence of various environmental problems in the world, global problems such as climate change create a number of difficulties in landscaping, choosing plants and presenting an aesthetic appearance to the environment. Along with scenic trees, the use of beautiful flowering shrubs will increase the aesthetic value of landscaping. The development of breeding methods is considered one of the promising directions if the bioecological characteristics of ornamental plants are studied in the scientific research centers and institutions of the developed countries of the world.
Keywords: Campsis Radicans (Seem), China Wisteria - Wisteria Sinensis ( Sums ), Japanese Beauty – Lonicera Japonica (Thumb).